1996
DOI: 10.1515/bchm3.1996.377.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Recombinant Human Parathyroid Hormone in Solution Using Multidimensional NMR Spectroscopy

Abstract: The solution structure of human parathyroid hormone, in the form of recombinant prolyl-hPTH(1-84), has been investigated by multidimensional NMR spectroscopy under conditions (aqueous trifluoroethanol) which favour the structured-state of the protein. Spin systems were identified from 3D 1H DQF (double-quantum filtered)-COSY and TOCSY spectra and sequence-specific assignments were from 2D 1H phase-sensitive NOESY spectra. Signal overlap was resolved in a 3D-NOESY-TOCSY spectrum and assignments were confirmed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Recently, the structure analysis of the whole PTH was reported (Gronwald et al, 1996). With increasing interest in designing analogs of PTH for therapeutic use, the elucidated structure obtained in the present study may prove helpful in probing appropriate directions for future PTH analog design.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recently, the structure analysis of the whole PTH was reported (Gronwald et al, 1996). With increasing interest in designing analogs of PTH for therapeutic use, the elucidated structure obtained in the present study may prove helpful in probing appropriate directions for future PTH analog design.…”
Section: Discussionmentioning
confidence: 72%
“…Such a conformational change was not observed for hPTH-(1-34). It takes directly an a-helical structure with SDS micelle as reported previously (Gronwald et al, 1996). The primary structure of cPTH-(1-34) differs from those of the other PTH fragments in the lack of the tribasic region (25)(26)(27).…”
Section: Discussionmentioning
confidence: 80%
“…The structure of PTH as it is bound to the P1R is not known, but NMR analyses of PTH analogs in a variety of polar and non-polar solvents suggest that the N-terminal portion of PTH (within residues Ser 3 to Lys 13 ) contains a short segment of ␣-helix. This segment is connected by a flexible bend or turn segment to a longer ␣-helix in the C-terminal portion of the molecule (within residues Ser 17 to Val 31 (12)(13)(14)(15)(16)(17)(18)). A recent crystallographic study of PTH(1-34) reveals a continuous helical structure that extends nearly the full length of the molecule (Ser 3 to Asn 33 ) with only a slight (15°) bend at the midsection (19).…”
mentioning
confidence: 99%
“…In a recent series of studies on the PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) scaffold peptide, we showed that certain substitutions at several sites in the peptide resulted in enhanced potency (23)(24)(25). The most potent PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) analog thus identified was [Ala 3,12 ,Gln 10 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)), which is 1,600-fold more potent than native PTH (1)(2)(3)…”
mentioning
confidence: 99%
“…Understanding hormone-PTH1R and PTH1R-G protein interactions has relied largely on determination of functional consequences resulting from mutations in either the hormone or the receptor (13,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), analysis of receptor fragments after cross-linking to radioiodinated, p-benzoyl-L-phenylalaninemodified ligands (13,(37)(38)(39)(40), crystallographic resolution of PTH (41), and NMR of PTH (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), PTHrP (59 -68), and short segments of the PTH1R (see Refs. 69 and 70 and for review see Refs.…”
Section: The Parathyroid Hormone (Pth)mentioning
confidence: 99%